Le « travail d’orientation ». Cultures professionnelles en tension dans l’orientation scolaire de jeunes migrants : une étude de cas - Aksel Kilic (Cahiers de la Recherche sur l'Education et les Savoirs)
The purpose of this article is to define, based on a case study carried out in two colleges with contrasting backgrounds, the content of what UPE2A teachers and headteachers refer to as “guidance work”, that is to say the work carried out to support the orientation of pupils. The article deals with the way in which UPE2A teachers and school heads position themselves in the division of labor for the guidance of migrant students according to their professional culture. For teachers, the objective is to support pupils in order to achieve an orientation that they themselves call “chosen”, i.e. corresponding to the tastes and ambitions of pupils and following a meritocratic ideal. The heads of establishments, for their part, assume a guidance that the actors call “typed”. This corresponds to a more realistic version of the guidance of these young migrants and considers the local training market after the ninth grade.